2021
DOI: 10.1021/acsnano.0c08510
|View full text |Cite
|
Sign up to set email alerts
|

From Protein Building Blocks to Functional Materials

Abstract: Proteins are the fundamental building blocks for high-performance materials in nature. Such materials fulfill structural roles, as in the case of silk and collagen, and can generate active structures including the cytoskeleton. Attention is increasingly turning to this versatile class of molecules for the synthesis of next-generation green functional materials for a range of applications. Protein nanofibrils are a fundamental supramolecular unit from which many macroscopic protein materials are formed. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
96
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 178 publications
0
96
0
Order By: Relevance
“…Previously we have reported different crosslinking regimes, physical or enzymatic, for the templating of protein microgels. [ 4,20,21 ] Transglutaminase solution was used to enzymatically crosslink the physically crosslinked microrods from their surfaces, and this enzyme catalyses the formation of covalent N ε‐(γ‐glutamyl) lysine amide bonds between the gelatin strands to form a permanent network of polypeptides (Figure , Supporting Information). [ 4,20,22 ] The physically and enzymatically crosslinked microrods did not undergo a gel–sol transition when heated to 37 °C, as they were more thermostable (Figure , Supporting Information) than the physically crosslinked microgels (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…Previously we have reported different crosslinking regimes, physical or enzymatic, for the templating of protein microgels. [ 4,20,21 ] Transglutaminase solution was used to enzymatically crosslink the physically crosslinked microrods from their surfaces, and this enzyme catalyses the formation of covalent N ε‐(γ‐glutamyl) lysine amide bonds between the gelatin strands to form a permanent network of polypeptides (Figure , Supporting Information). [ 4,20,22 ] The physically and enzymatically crosslinked microrods did not undergo a gel–sol transition when heated to 37 °C, as they were more thermostable (Figure , Supporting Information) than the physically crosslinked microgels (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…The collagen triple helices form the "building blocks" of tissues, namely fibrils and fibers. Furthermore, the collagen nanofibrils can be used for obtaining various functional materials (e.g., gels, films, and microgels) [1]. Interestingly, the molecular dynamics (MD) calculations results reported by Mathavi et al (2019) [2] showed that the collagen self-assemblies are stabilized by the interchain water-mediated hydrogen bonds (H-bonds).…”
Section: Introductionmentioning
confidence: 99%
“… 29 , 30 In general, protein amyloids are extremely versatile, due to the functional diversity in the protein/peptide moieties they are formed from; this has led to their application in areas such as catalysis, filtration, drug delivery, and biomimetic functional materials. 31 , 32 To this end, lysozyme has gained particular interest for its ability to rapidly form amyloid aggregates with broad spectrum antibacterial resistance. 33 36 This is of particular interest as lysozyme in its native form demonstrates little to no antibacterial efficacy against Gram-negative bacteria.…”
Section: Introductionmentioning
confidence: 99%